ANALISIS KUALITAS PELAYANAN DALAM MENINGKATKAN KEPUASAN PELANGGAN PADA CV TRESMO LAUNDRY BANJARMASIN - Ni Nyoman Suarniki; Rika Sylvia; Dewi Setiawati; Untari Okta Eka Wardhani (Dinamika Ekonomi: Jurnal Ekonomi dan Bisnis, 2025)
This study aims to evaluate service quality in improving customer satisfaction at CV Tresmo Laundry Banjarmasin. The method used was descriptive qualitative, with data collected through questionnaires distributed to 100 respondents using a purposive sampling technique. The analysis was conducted based on the SERVQUAL model, which encompasses five dimensions: tangibles, reliability, responsiveness, assurance, and empathy. The results showed that each service quality dimension received a fairly good average score (3.57–3.66), while the customer satisfaction indicator also fell within the fairly satisfactory category (3.54–3.68). These findings the close relationship between service quality and customer satisfaction, improving reliability, responsiveness, and empathy has the potential to strengthen customer loyalty. Service quality management so that CV Tresmo Laundry can maintain customer satisfaction and strengthen its competitiveness in the competitive laundry industry.